PENERAPAN BANK TANAH DAN PENYELESAIAN SENGKETA TANAH DI LAMONGAN SETELAH BERLAKUNYA UU NO 6 TAHUN 2023 - Purnomo, Galih Eko; Babusallam, Basuki (Journal of Mandalika Literature, 2023)
Land issues have always been actual and complex issues. Factors that hinder population growth often occur due to the lack of additional housing, economic income of the population, as well as the need for infrastructure to support space, and the ease of access to land. Land availability has often been complicated in recent years by both local and central governments. The UUPA mandates that the state can only procure land, not as a land owner. This study the author used normative, comparative and factual methods. Seeing the complicated problems that often occur in the community requires methods, and other ways to reduce basic, effective, efficient land problems. The concept of the Land Bank itself is urgent to be practiced in Indonesia as an alternative way to provide land to carry out national development. Land Bank means as a reserve of government or private land that is carried out for development activities and avoids the possibility of soaring land prices. The Land Bank's own method is to control the land market and the balance of local market land. Therefore, the need for legal protection for the implementation of Bank Tanah Indonesia and regulations related to institutions authorized to carry out the implementation of the Land Bank's work pact.